Evaluating the Mechanical Properties of Concrete with the use of Coconut Fiber - Joshi, Khem Raj; Mandal, Bharat; Ghoshal, Tarumay (Nepal Journal of Science and Technology, 2023)
Coconut fiber is readily available, it is a good substitute for steel fiber in concrete. Additionally, it offers coconut farmers a new revenue stream as demand from the construction sector increases. These natural fibers can be a cost-effective way to dispose of coir mattress waste and, being environmentally friendly, they can significantly reduce environment pollution from burning it. However, it is crucial to assess whether the use of these fibers affects the strength of concrete, determining their suitability for widespread use in the construction industry or identifying potential concerns. This study aims to compare the strength of reinforced concrete without coconut fiber to that with coconut fiber reinforced concrete at various fiber concentrations. Tests were conducted with different fiber percentages (1%, 3%, and 5% by weight of cement) to evaluate the compressive, split tensile, and flexural strength of coconut fiber reinforced concrete. The results indicate that coconut fiber enhances both the flexural and compressive strength of concrete, along with improving its ductile behavior.